Prognostic relevance of the flow cytometric count of medullar blasts in myelodysplastic syndromes. (4th December 2014) - Molteni, Alfredo; Riva, Marta; Cesana, Clara; Speziale, Valentina; Nichelatti, Michele; Scarpati, Barbara; Greco, Rosa; Ravano, Emanuele; Cairoli, Roberto; Rossini, Silvano; Morra, Enrica
Abstract Objective The medullar blast count is a milestone in the prognostic assessment in myelodysplastic syndromes (MDS). The optical microscopy (OM) may sometimes be inaccurate in this disease. The aim of this work is to test the flow immunocytometric (FCM) determinations of medullar immature cells (CD45±) and the expression, among them, of CD33, CD34, and CD117 markers, for their prognostic relevance. Methods In a retrospective analysis of 98 patients affected by MDS, the IPSS was re‐calculated by means of the FCM determination of blasts. Survival of patients at low or intermediate‐1 IPSS risk was compared with the survival of patients at intermediate‐2 or high IPSS risk. In the 64 cases with OM blast count lower than 5%, the survival of patients with the FCM count of medullar blasts ≤2% was compared with that of patients with FCM count >2%. Results Each single marker had a prognostic weight comparable to the optical blast count. The FCM blast count was particularly efficient in distinguishing the risk of having up to 2% or more than 2% of blasts in patients without OM excess of blasts. Conclusion This method is interesting as prognostic tool, especially in patients without excess of blast.